Agricultural marketing in Africa - Whetham, Edith Holt. (London : Oxford University Press, 1972)
African agricultural marketing systems are described with emphasis on domestic markets in foods.
Includes bibliographical references.
SJU
Loans
Keywords: Farm produce; Produce trade; Agriculture